2005
DOI: 10.2298/hel0542075a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bavistin and dithane m-45 on the Mycorrhizae and Rhizosphere microbes of sunflower

Abstract: In the present investigation, two fungicides viz. Bavistin and Dithane M-45 were tested for the effect on soil mycoflora with special reference to mycorrhizal fungi of sunflower crop. It was evident from the results that the two fungicides had different effects on soil mycoflora. Reduction of various species of soil fungi was more extensive in first twenty days in comparison with the later half of the experimental period. The fungicidal effect of both fungicides decreased with increase of time and it resulted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Soil nematodes, earthworms and protozoa are affected by field application rates of the fungicide fenpropimorph and other herbicides. Application of fungicide, carbendazim resulted in reduction of various species of soil fungi extensively in first 20 days (Aggarwal et al, 2005). It was reported that Prosulfuron, an herbicide inhibited N 2 O and NO production by the bacteria (Kinney et al 2005).…”
Section: Ansfmentioning
confidence: 99%
“…Soil nematodes, earthworms and protozoa are affected by field application rates of the fungicide fenpropimorph and other herbicides. Application of fungicide, carbendazim resulted in reduction of various species of soil fungi extensively in first 20 days (Aggarwal et al, 2005). It was reported that Prosulfuron, an herbicide inhibited N 2 O and NO production by the bacteria (Kinney et al 2005).…”
Section: Ansfmentioning
confidence: 99%
“…The fungi-toxic effect of carbendazim decreased with increased time, and resulted in the reappearance of certain fungi after a particular time. A reduction in various species of soil fungi was more extensive in the first 20 days than in the latter half of the experimental period with the fungicide, carbendazim (Aggarwal et al 2005).…”
Section: Resultsmentioning
confidence: 92%
“…It is known that pesticide residues impair the growth and metabolic activities of arbuscular mycorrhizae, root colonizing microorganisms and a small number of algae and fungi species (DHANANJAYAN et al 2020). It has been determined that carbendazim and mancozeb, which are fungicides, negatively affect the number of mycorrhizal spores and mycorrhizal root colonization on the face and reduce the growth of sunflowers (AGGARWAL, 2005). Similarly, studies on the effect of herbicides on mycorrhizae have reported that oxyfluorfen and oxadiazon promote the microbial population and can increase the presence of phosphorus (P) in rice.…”
Section: Effects Of Pesticides On Soil Organismsmentioning
confidence: 99%